Optimization and engineering verification of excitation scheme for aircraft ground vibration test - CHEN Haoyu; WANG Binwen; SONG Qiaozhi; LI Xiaodong (Hangkong gongcheng jinzhan)
Ground vibration test is an important part of aircraft model development and strength verification. In aircraft ground vibration test，an appropriate excitation scheme can significantly shorten the test's period and improve the accuracy of mode identification. In this paper，QR decomposition based on the finite element model is used for global planning of exciter placement，and mode participation is introduced to evaluate the plan's exciting efficiency. The multivariate mode indicator function is used to optimize the exciting force vector for closely spaced modes. Finally，these methods are verified in a small general aircraft's ground vibration test，which significantly improves the test's efficiency and reduces the difficulty of closely spaced modes identification. The excitation scheme optimization method adopted in this article has high engineering application value.